Everyday cognitive failure in patients suffering from neurosarcoidosis: Cognitive failure in neurosarcoidosis - Voortman, Mareye; de Vries, Jolanda; Hendriks, Celine M.R.; Elfferich, Marjon D.P.; Wijnen, Petal A.H.M.; Drent, Marjolein (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: Cognitive failure is associated with memory and concentration problems. Previously, a prevalence of one third was found in a general sarcoidosis population. The aim of this study was to assess if neurosarcoidosis patients are at higher risk for developing everyday cognitive failure using the Cognitive Failure Questionnaire (CFQ) and to determine what factors were associated with cognitive failure. Methods: A cross-sectional web-based survey was conducted from April to May 2017 in a national sample of neurosarcoidosis patients. The survey asked about complaints and included 3 questionnaires (Fatigue Assessment Scale [FAS], Small Fiber Neuropathy Screening List [SFNSL] and CFQ. Data were compared to a general sarcoidosis population. Results: Of the 152 patients who completed the survey, 131 had neurosarcoidosis. The mean CFQ score was significantly higher in the neurosarcoidosis (45.6±20.7) compared to the general sarcoidosis population (36.2±15.9; p< 0.0001). High CFQ scores (≥43) were found in 55.7% and 33.9%, respectively (p<0.0001). The FAS score (OR 21.4) and SFNSL score (OR 4.3) were the strongest positive predictors of a high CFQ score. Conclusion: Cognitive failure is a significant problem in neurosarcoidosis. More than half of the patients reported cognitive deficits, compared to one third of a general sarcoidosis population. Fatigue and small fiber neuropathy play a role in cognitive failure.